Peluang dan Tantangan Pengintegrasian Kecerdasan Buatan dalam Pendidikan Literasi Informasi - Ismaya; Ridwan, Madinatul Munawwarah; Galib, Andi Ahmad Chabir; Syahdan (UPT Perpustakaan UIN Alauddin Makassar, 2025)
This study aims to analyze the integration of artificial intelligence (AI) in information literacy education, specifically to understand the experiences and perspectives of students at Universitas Muhammadiyah Enrekang regarding the implementation of this technology. The research employs a case study method with a qualitative approach, collecting data through interviews and thematic document analysis. The analysis process involves identifying patterns or themes in the text through selection, coding, and interpretation to gain a deeper understanding of its meaning and context. The findings indicate that AI integration in information literacy education has the potential to enhance accessibility, efficiency, and learning quality. The majority of students responded positively to AI technology, highlighting benefits such as faster and more relevant information access as well as personalized feedback. This suggests that AI can serve as a valuable tool in improving education quality and fostering innovation in learning. However, several challenges remain in AI integration, including data privacy concerns, technological sustainability, and resource disparities. Therefore, further research is recommended to explore the perspectives of other stakeholders and examine AI applications in various educational contexts.